The innocents abroad - Twain, Mark, 1835-1910 (Penguin classics., 2002)
"Based on a series of letters Mark Twain wrote from Europe for San Francisco and New York newspapers as a roving correspondent, The Innocents Abroad (1869) is a caricature of the sentimental travel books popular in the mid-nineteenth century. Mark Twain's fresh and humorous perspective on hallowed European landmarks lacked reverence for the past, and was as mocking about American manners (including his own) as it was about European attitudes. Twain ultimately concludes that, for better or worse, "Human nature is very much the same all over the world.""--Jacket.